Depth Advanced Control of an Autonomous Underwater Robot (Aintelia Science Notes, 2024)
This autonomous underwater robot control is a very challenging task because of autonomous underwater robotsystem nonlinearity, time-variance, uncertain external disturbance and difficulty in hydrodynamic modeling.Based on detailed autonomous underwater robot control survey and description of autonomous underwaterrobot dynamics, this paper proposes to introduce new control law algorithm based on high order sliding modes(HOSM) for depth control of the autonomous underwater robot. A comparison with classical sliding mode(SM) is carried out as well. These control techniques are based on second order sliding modes. High ordermethods allow overcoming the chattering effect by removing the discontinuity of the control vector. We showthat these high order controllers hold the properties of classical SM control laws and remove chatteringproblem. Different simulations have been carried out to show the performance and effectiveness of theproposed method.